The Politics of Hung Authorities - Leach, Steve. author. aut Link
VII, 243 p.
Keywords: In the 1980s there was a marked increase in the number of hung local authorities or authorities in which there was no clear majority. This book describes the different patterns of hungness and the response of local authorities to the new situation.